A monoclonal antibody specific for prophase phosphorylation of histone deacetylase 1: a readout for early mitotic cells. Issue 1 (2nd January 2016) - Segré, Chiara V.; Senese, Silvia; Loponte, Sara; Santaguida, Stefano; Soffientini, Paolo; Grigorean, Gabriela; Cinquanta, Mario; Ossolengo, Giuseppe; Seiser, Christian; Chiocca, Susanna
Abstract : Histone deacetylases (HDACs) are modification enzymes that regulate a plethora of biological processes. HDAC1, a crucial epigenetic modifier, is deregulated in cancer and subjected to a variety of post-translational modifications. Here, we describe the generation of a new monoclonal antibody that specifically recognizes a novel highly dynamic prophase phosphorylation of serine 406-HDAC1, providing a powerful tool for detecting early mitotic cells.